PENERAPAN PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN MATEMATIKA MATERI BANGUN DATAR SD NEGERI 72 PALEMBANG - Inka Citia Endini; Muhammad Juliyansyah Putra; Nora Surmilasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools plays an important role in developing students' logical, critical, and problem-solving thinking skills. However, learning still focuses on memorizing formulas without a deep understanding of concepts, especially in plane geometry material, resulting in low student learning outcomes. One alternative to address this problem is the implementation of the Deep Learning approach, which emphasizes conceptual understanding, active involvement, and meaningful learning experiences. This study aims to analyze the effect of the implementation of the Deep Learning approach on student learning outcomes in plane geometry material. The study used a quantitative method with a pre-experimental type and a one-group pretest-posttest design. The research subjects were 32 fifth-grade students of SD Negeri 72 Palembang. Data were collected through learning outcome tests and observation sheets, then analyzed using normality tests, homogeneity tests, and Paired Sample T-Tests. The results showed an average pretest score of 60.55, increasing to 69.42 in the posttest. A significance value of 0.000 <0.05 indicates a significant effect of the implementation of the Deep Learning approach on student learning outcomes. The Effect Size value of 1.26 is considered large, indicating that the Deep Learning approach is effective in improving student learning outcomes.